1986
DOI: 10.1128/jcm.24.4.677-679.1986
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of influenza virus by shell vial assay with monoclonal antibodies

Abstract: Of 45 influenza virus strains (43 type A and 2 type B) detected in conventional tube cell cultures (average time, 4 days), 25 (56%) were detected by immunofluorescence in the shell vial assay 24 h postinoculation. The specific fluorescence produced should allow this procedure to be readily adapted by laboratories with various degrees of experience with immunofluorescence methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…Commercially available R-Mix cells (Diagnostic Hybrids Inc., Athens, OH), a mixture of A549 and Mink lung cells, have been used extensively by clinical laboratories for the detection of the eight viruses that are detected by DFA (84,297). The advantage of SVC is that most viruses can be identified in 18 to 48 h, compared with 4 to 14 days for traditional tube culture (75). The disadvantage of SVC is that some viruses do not replicate robustly in R-Mix cells, and if viruses need to be recovered for further analysis, they need to be passaged in R-Mix Too cells or primary monkey kidney cells (228).…”
Section: Influenza Virusmentioning
confidence: 99%
“…Commercially available R-Mix cells (Diagnostic Hybrids Inc., Athens, OH), a mixture of A549 and Mink lung cells, have been used extensively by clinical laboratories for the detection of the eight viruses that are detected by DFA (84,297). The advantage of SVC is that most viruses can be identified in 18 to 48 h, compared with 4 to 14 days for traditional tube culture (75). The disadvantage of SVC is that some viruses do not replicate robustly in R-Mix cells, and if viruses need to be recovered for further analysis, they need to be passaged in R-Mix Too cells or primary monkey kidney cells (228).…”
Section: Influenza Virusmentioning
confidence: 99%
“…By changing the cell line grown on the coverslip and the specificity of the MAbs used for staining, detection of other viruses was easily facilitated. HSV (63), influenza virus (45,130), mumps virus (56), various respiratory viruses (108,117,126), enteroviruses (155), adenoviruses (155), dengue virus (136), and VZV (15,161) have been isolated in shell vials. Recent studies by Landry et al (85) demonstrated the ability to detect hMPV by day 2 postinoculation in A549, HEp-2, and LLC-MK2 shell vials when stained with a MAb (MAb 8510; Chemicon International, Temecula, CA) to hMPV matrix protein.…”
Section: Centrifugation-enhanced Inoculation and Pre-cpe Detection Ofmentioning
confidence: 99%
“…Human influenza A virus strains are further'clas&ied in the subtypes HlNl, H3N2 and the presently not circulating H2N2 subtype, based on the antigenic differences of the hemagglutinin (H) and the neuraminidase (N) surface proteins. Laboratory diagnosis of infections with influenza virus is mainly performed by culturing a respiratory sample, nasopharyngeal aspirates or swabs, for 16 24 h, with, subsequently, an immunofluorescent analysis of the propagated virus or by direct immunofluorescence (Espy et al, 1986;Stokes et al, 1988). Recently, the polymerase chain reaction '(PCR) has ,b&n used for detection of numerous pathogens and the"technique appeared to be very sensitive and specific (Wright and Wynford-Thomas, 1990).…”
Section: Introductionmentioning
confidence: 99%